Sustainable Engineering Practices in Construction: A Systematic Review of Green Building Materials and Techniques - Ilham Ilham (Penelitian dan Pengembangan Ilmu, 2024)
The construction industry is one of the largest contributors to global carbon emissions, and efforts to reduce the sector's environmental impact are increasingly urgent. This study aims to identify the perceptions and obstacles faced by stakeholders in adopting green building materials that focus on carbon reduction, using the approach systematic literature review. By analyzing 50 relevant recent studies from various geographic contexts, this research finds that perceptions of negative related costs, technical obstacles, and lack of managerial support are significant obstacles in the implementation of green materials. The implications of these findings provide policy and practice recommendations to encourage the adoption of environmentally friendly materials through financial incentives, outreach on the benefits of sustainability, and technical training in the construction industry.